Neuroendocrine Disruption of Organizational and Activational Hormone Programming in Poikilothermic Vertebrates - Rosenfeld, Cheryl S. (J Toxicol Environ Health B Crit Rev, 2017)
In vertebrates, sexual differentiation of the reproductive system and brain is tightly orchestrated by organizational and activational effects of endogenous hormones. In mammals and birds, the organizational period is typified by a surge of sex hormones during differentiation of specific neural circuits; whereas activational effects are dependent upon later increases in these same hormones at sexual maturation. Depending on the reproductive organ or brain region, initial programming events may be modulated by androgens or require conversion of androgens to estrogens. The prevailing notion based upon findings in mammalian models is that male brain is sculpted to undergo masculinization and defeminization. In absence of these responses, the female brain develops. While timing of organizational and activational events vary across taxa, there are shared features. Further, exposure of different animal models to environmental chemicals such as xenoestrogens such as bisphenol A- BPA and ethinylestradiol- EE2, gestagens, and thyroid hormone disruptors, broadly classified as neuroendocrine disrupting chemicals (NED), during these critical periods may result in similar alterations in brain structure, function, and consequently, behaviors. Organizational effects of neuroendocrine systems in mammals and birds appear to be permanent, whereas teleost fish neuroendocrine systems exhibit plasticity. While there are fewer NED studies in amphibians and reptiles, data suggest that NED disrupt normal organizational-activational effects of endogenous hormones, although it remains to be determined if these disturbances are reversible. The aim of this review is to examine how various environmental chemicals may interrupt normal organizational and activational events in poikilothermic vertebrates. By altering such processes, these chemicals may affect reproductive health of an animal and result in compromised populations and ecosystem-level effects.